Late Steps in the cytosolic Iron-Sulfur Cluster Assembly in Trypanosoma brucei - Haindrich, Alexander Christoph (Jihočeská univerzita, 2016)
The aim of this thesis was to investigate genes involved in the late steps of the Cytosolic Iron sulfur cluster Assembly (CIA) pathway in procyclic T. brucei, to determine their cellular localization and find their possible interaction partners and substrates.
Late Steps in the cytosolic Iron-Sulfur Cluster Assembly in Trypanosoma brucei
Keywords: FeS cluster; CIA pathway; Tryanosoma brucei; FeS cluster; CIA pathway; Tryanosoma brucei